Electrical characterization of Bi1.50-xYxZn0.92Nb1.5O6.92 varactors - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2014)
The electrical properties of yttrium doped bismuth zinc niobium oxide (BZN) pyrochlore ceramics are explored by means of temperature dependent electrical conductivity dielectric constant and capacitance spectra in the frequency range of 0-3 GHz. It is observed that the doped BZN exhibit a conductivity type conversion from intrinsic to extrinsic as the doping content increased from 0.04 to 0.06. The thermal energy bandgap of the intrinsic type is 3.45 eV. The pyrochlore is observed to exhibit a dielectric breakdown at 395 K. In addition, a negative capacitance (NC) spectrum with main resonance peak position of 23.2 MHz is detected. The NC effect is ascribed to the increased polarization and the availability of more free carriers in the device. When the NC signal amplitude is attenuated in the range of 0-20 dBm at 50 MHz and 150 MHz, wide tunability is monitored. Such characteristics of the Y-doped BZN are attractive for using them to cancel the positive parasitic capacitance of electronic circuits. The canceling of parasitic capacitance improves the high frequency performance of filter inductors and reduces the common mode noise of the resonance signal.
Keywords: Yttrium doping; electrical conductivity; microwave cavity; varactors; NEGATIVE-CAPACITANCE; PYROCHLORE CERAMICS; FREQUENCY; RANGE